Improving Utilization of Aspirin for Prevention of Preeclampsia in a High-Risk Urban Cohort: A Prospective Cohort Study - Boelig, Rupsa C.; Wanees, Mariam; Zhan, Tingting; Berghella, Vincenzo; Roman, Amanda (American Journal of Perinatology, 2020)
Objective This study aimed to evaluate the utilization of aspirin for preeclampsia prevention before and after implementation of a screening tool during nuchal translucency (NT) ultrasound.Study Design One-year prospective cohort study of patients at high risk for preeclampsia after the implementation of a screening tool (postscreen) administered to all patients at check in for NT (11–13 weeks) ultrasound. Prospective cohort was compared with one-year retrospective cohort (prescreen) the year prior (2017). All patients who presented for NT ultrasound in both cohorts were evaluated for the presence of one or more risk factor for preeclampsia with screening tool collected prospectively and chart review retrospectively. Provider recommendation for aspirin determined by documentation in prenatal record. Primary outcome was rate of provider recommendation for aspirin pre versus post screening tool, compared by Chi-square test and adjusted for potential confounders with multiple regression analysis.Results Pre- (n = 156) and postscreen (n = 136) cohorts were similar except for race and multifetal gestation. Prescreen, rate of provider recommendation for aspirin was 74%. Of those with prior preeclampsia, 96% were recommended aspirin, compared with 64% of patients with other risk factors (p < 0.001). Postscreen, provider recommendation of aspirin improved to 95% (p < 0.001). Rate of preeclampsia/gestational hypertension were similar between cohorts; however, there was a reduced adjusted risk in overall preterm birth <37 weeks (adjusted odds ratio [aOR] = 0.50 [0.25–0.99]) and preterm birth <34 weeks (aOR = 0.33 [0.13–0.88]) postscreening tool implementation.Conclusion Prior to implementation of a simple screening questionnaire, approximately 25% of high risk patients did not receive the recommendation of aspirin for preeclampsia prevention. High-risk patients who lack a history of preeclampsia were less likely to be advised of aspirin prophylaxis. Use of a simple universal screening tool at time of NT ultrasound significantly improved utilization of aspirin for preeclampsia prevention and may improve patient outcomes.Key Points
Keywords: aspirin; preeclampsia; implementation research